OBJECTIFICATION OF THE ABILITY TO PROVIDE FOR PARAMETERS: CONSTRUCTION OF QUANTITATIVE INDICATORS IN INDONESIAN MARRIAGE LAW - Fanridhal Engo (QANUN: Journal of Islamic Laws and Studies, 2026)
This study aims to analyze the concept of "ability to provide for one" in Indonesian marriage law and formulate objective indicators to overcome legal uncertainty due to norm abstraction. Using normative juridical methods with conceptual and comparative approaches, this study examines Law Number 1 of 1974 and the Compilation of Islamic Law as primary legal materials. The findings of the study show that the phrase "according to ability" in Article 34 of the Marriage Law and Article 80 of the KHI is still abstract, thus triggering disparities in judges' decisions and neglect of the economic rights of wives and children. Although the Supreme Court has sought objectification through SEMA Number 3 of 2015 and jurisprudence, the standardization has not been systematically integrated within a normative framework. In conclusion, this study emphasizes that the determination of alimony must transform from the judge's subjective discretion to the use of measurable quantitative indicators, such as the standard of Decent Living Needs (KHL), the husband's actual income, and the inflation rate. The academic contribution of this research lies in the offer of a jurimetry-based reconstruction model of the concept of livelihood that unites the principles of theological justice (Islamic nomocracy) with modern legal certainty. Through this quantitative approach, the fulfillment of alimony not only functions as a legal instrument, but also as a preventive effort against the degradation of family welfare and social problems.